ЛИРИКА ФАРИДЫ АФРУЗ (Scientific journal of the Fergana State University, 2023)
This article examines the creative biography of Farida Afruz, also the peculiarities of poems of the poetess. An attempt to explain the genre of “fikhra” and “tasbekh” as genres of artistic lyrics is made.